Resident Memory-Like Tumor-Infiltrating Lymphocytes (TILRM): Latest Players in the Immuno-Oncology Repertoire - Smazynski, Julian; Webb, John R. (Frontiers in Immunology, 2018)
Resident memory T cells (TRM) are a recently identified subset of long lived memory T cells that are characterized in terms of their unique surface phenotype combined with a non-recirculating pattern of localization to non-lymphoid, peripheral tissues. TRM have quickly become a key area of focus in understanding immune responses to microbial infection in so called ‘barrier’ tissues, and appear to be particularly critical for protection against repeat exposure at the same site. More recently, tumor infiltrating T cells with canonical TRM features are being identified in human cancers, in particular cancers of epithelial origin, and their presence is broadly found to be associated with favorable long term prognosis. In addition, recent studies have found that these tumor infiltrating TRM (TILRM) are uniquely activated in melanoma patients undergoing PD-1 directed checkpoint blockade therapy. Accordingly, there is much interest at present regarding the biology of these cells and their role in anti-cancer immunity. Herein, we review the current state of the literature regarding TILRM with a specific emphasis on their specificity, origins and relationship to conventional pathogen-specific TILRM and speculate upon the way(s) in which they might contribute to improved prognosis for cancer patients. We discuss the growing body of evidence that suggests TILRM may represent a population of bona-fide tumor reactive T cells and the attractive possibility of leveraging this cell population for future immunotherapy.